Adsorption of Bentazone from Aqueous Solutions Using Silica Particles - Spaltro, Agustín (2015)
Among various water purification and recycling technologies, adsorption is a fast, inexpensive and universal method. The development of low-cost adsorbents has led to the rapid growth of research interests in this field. We have studied the kinetics and thermodynamics of the adsorption of bentazone on silica as a function of agitation time, adsorbent dose and temperature in a batch process. We tried to find the best fitting between experimental data and several theoretical models (Langmuir, Freundlich, Brunauer-Emmett-Teller (BET) and Temkin). As a result, the adsorption isotherms follow a BET model. The adsorption kinetics was analyzed by using pseudo first order and pseudo second order models. Thermodynamic parameters of adsorption process (∆G, ∆S and ∆H) were computed. The effect of contact time on the removal efficiency of studied substances was investigated. The highest removal efficiency of bentazone was achieved by the adsorption on silica particles. The adsorbent investigated exhibited potential applications in water decontamination and treatment of industrial and agricultural waste waters.